Environmental anomalies in the northeastern East China Sea during the last 3 000 years: implications for El Nino activity in the Holocene - Chang, Fengming; Li, Tiegang; Zhuang, Lihua; Yan, Jun (Chinese Journal of Oceanology and Limnology, 2010)
To reconstruct the productivity changes for the last 10 500 a in the northeastern East China Sea (ECS), biogenic compounds (such as carbonate, organic carbon and opal), marine micropaleontological fossils (planktonic foraminifera, benthic foraminifera, radiolarian and silicoflagellate) and the compositional characters of benthic foraminifera fauna analyses were carried out on a sediment core DOC082 obtained from the western slope of Okinawa Trough (29 degrees 13.93'N, 128 degrees 08.53' E; 1 128 m water depth). The long-term changes of biogenic and micropaleontological proxies display some similarities through the last 10 500 a, which show three different phases: lower values are recorded during the early and middle Holocene (before about 4 000 a BP), followed by an abrupt and remarkable increase at about 4 000 a BP, the late Holocene (after about 3 000 a BP) is characterized by continuously high values. The multi-proxy data of paleoproductivity and percents of benthic foraminifera genera (Uvigerina and Bulimina) show that during the early and middle Holocene (10 500-4 000 a BP) productivity was relatively low with a sudden and distinct increase at about 4 000 a BP, and the late Holocene (3 400-0 a BP) is marked by significantly higher productivity. Also, the radiolarian-based sea surface temperature (SST) records reveal a distinct decline in SST in the late Holocene after 3 200 a BP, very different from the early and middle Holocene. For the last 3 000 a, the enhanced biological productivity and distinctly lower SST indicate a major change of oceanographic conditions in the northeastern ECS. These marine environmental anomalies are consistent with other paleoclimatic records for the late Holocene in the Chinese continent and its surrounding regions. After analyzing the mechanisms of modern productivity and SST changes in the northeastern ECS, and based on the climatic anomalies in the Chinese continent and variations in the Kuroshio Current during modern El Nino periods, we suggest that the anomalous environmental conditions in the northeastern ECS may imply intensified El Nino activity during the late Holocene.
id: 1927; PT: J; UT: WOS:000275654100024